The use of dried blood spots for the serological evaluation of SARS-CoV-2 antibodies. (22nd February 2021) - Toh, Zheng Quan; Higgins, Rachel A; Anderson, Jeremy; Mazarakis, Nadia; Do, Lien Anh Ha; Rautenbacher, Karin; Ramos, Pedro; Dohle, Kate; Tosif, Shidan; Crawford, Nigel; Mulholland, Kim; Licciardi, Paul V
Abstract: Background: To determine if dried blood spot specimens (DBS) can reliably detect severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibodies, we compared the SARS-CoV-2 IgG antibody response in paired serum and eluates from DBS specimens. Methods: A total of 95 paired DBS and serum samples were collected from 74 participants (aged 1–63 years) as part of a household cohort study in Melbourne, Australia. SARS-CoV-2 IgG antibodies specific for the receptor-binding domain (RBD) and S1 proteins between serum and eluates from DBS specimens were compared using an FDA-approved ELISA method. Results: Among the 74 participants, 42% (31/74) were children and the rest were adults. A total of 16 children and 13 adults were SARS-CoV-2 positive by polymerase chain reaction. The IgG seropositivity rate was similar between serum and DBS specimens (18.9% (18/95) versus 16.8% (16/95)), respectively. Similar RBD and S1-specific IgG levels were detected between serum and DBS specimens. Serum IgG levels strongly correlated with DBS IgG levels (r = 0.99, P < 0.0001) for both SARS-CoV-2 proteins. Furthermore, antibodies remained stable in DBS specimens for >3 months. Conclusions: DBS specimens can be reliably used as an alternative to serum samples for SARS-CoV-2 antibody measurement. The use of DBS specimens would facilitate serosurveillance efforts particularly in hard-to-reach populations and inform public health responses including COVID-19 vaccination strategies.